Changes in vegetation and soil properties following 6 years of enclosure in riparian corridors. (6th March 2020) - Wang, Di; Zhang, Yi-Ran; Feng, Yu-Long; Liu, Zhi; Qu, Bo
Abstract: Aims: Riparian corridors play vital roles in the maintenance of biodiversity. Nonetheless, plant species diversity and vegetation coverage in riparian corridors are seriously threatened by increasing pressure owing to livestock consumption and anthropogenic disturbance; even the stability of river courses has been threatened. The establishment of enclosures is a widely used strategy to restore degraded grassland ecosystems, but its impact on degraded herbaceous riparian vegetation and soil properties remains unclear. The aim of this study was to evaluate whether species composition, richness, diversity, and soil properties can be recovered by the enclosure. Methods: Twenty long-term monitoring sample plots were set in the Liaohe main stream river, Liaohe main stream river was enclosed for grazing and farmland exclusion in 2012. The height, coverage and individual numbers of plant were recorded for species richness and diversity evaluation from 2012 to 2017; soil nutrients were measured for comparative analysis in 2012 and 2017. We examined the effects of the establishment of enclosures on plant species diversity and soil properties from 2012 to 2017 in the riparian corridors of the Liaohe River system in China. Important Findings: Plant species richness and diversity significantly increased from 2012 to 2017. The dominance of Asteraceae plants increased, while the abundance of Gramineae plants decreased over time. The difference in abundance increased each year since enclosure was implemented in 2012. The concentrations of phosphorus and potassium in the soil significantly decreased as a result of the combined effects of vegetation restoration and prohibition of farming practices following the establishment of enclosures. There was also a lag time related to the response of soil organic matter to the establishment of enclosures. In conclusion, our study provides new evidence regarding the response of species diversity, species composition and soil properties following riparian vegetation restoration efforts through enclosure development.